Poesia digital e tradução intersemiótica: um olhar sobre produções digitais de Clemente Padin, Joesér Alvarez e Fernando Aguiar - Vieira, Flaviano Maciel (2012)
This research aims to reflect on what has been called electronic or digital poetry and if it really is possible to make poetry drawn from signs generated by a computer support (bits and pixels on a computer screen). Are observed characteristics and conceptual ideas that are configured on the subject. Three objects of analysis are discussed (pancircular, of Clemente Padin, Oraculum of Joesér Alvarez and Soneto Digital, of Fernando Aguiar) so that they can apply the theoretical framework in a practical way, which is important for theoretical and conceptual consolidation. The theoretical perspective that underlies the research involves the Semiotics of Culture (Yuri Lótman, Uspênsky, Roman Jakobson, etc.), with incursions by Peircean semiotics.